2019
DOI: 10.1093/pm/pny240
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Opioid Dosing, Pain Severity, and Disability in a Community-Based Chronic Pain Population: An Exploratory Retrospective Analysis

Abstract: Objective. To determine the relationship between opioid dose change, pain severity, and function in patients with chronic pain. Design. Retrospective cohort study. Setting. Community interdisciplinary pain management practice. Subjects. A total of 778 patients with chronic pain prescribed opioids for three or more consecutive months between April 1, 2013, and March 1, 2015. Methods. Changes in opioid dose, pain severity rating, modified Roland Morris Disability Questionnaire score, and opioid risk data were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Among 3,155 potentially relevant citations, we included 49 studies-1 systematic review (Frank et al), 8 34 studies included in that systematic review,, and 14 new studies identified in our literature search. [50][51][52][53][54][55][56][57][58][59][60][61][62][63] A total of 40,245 patients are included in the 14 new studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 3,155 potentially relevant citations, we included 49 studies-1 systematic review (Frank et al), 8 34 studies included in that systematic review,, and 14 new studies identified in our literature search. [50][51][52][53][54][55][56][57][58][59][60][61][62][63] A total of 40,245 patients are included in the 14 new studies.…”
Section: Resultsmentioning
confidence: 99%
“…We prioritized evidence synthesis of: 1) studies conducted in a VHA setting or other outpatient settings; 2) studies that addressed serious harms such as overdose and suicide; and 3) studies that included enough detail regarding patient and tapering characteristics to evaluate the applicability of findings to VHA populations and settings. Nineteen studies (Table 1) (2 RCTs, 18, 50 6 controlled observational studies, 54,56,[60][61][62][63] and 11 uncontrolled observational studies) 27,30,32,34,36,40,55,[57][58][59]65 met these criteria, which we refer to as "prioritized studies." The remaining studies either had low applicability to VHA or outpatient settings or included patients or interventions that were not well-described.…”
Section: Resultsmentioning
confidence: 99%
“…To date, research into physical functioning in individuals with chronic pain and FM has mostly relied on self-report measures [ 25 , 41 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Performance-based measures, which focus on actual rather than perceived functional ability, have generally been neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Dose escalation was defined as at least a 20% increase in average daily MME dose in the second 180‐day period compared to the initial 180‐day period. Dose maintenance was defined as an average daily dose in the second period that was within ± 20% of the average daily dose of the initial period . Those who experienced a dose decrease of 20% or greater were excluded.…”
Section: Methodsmentioning
confidence: 99%